TRPA1 activation in a human sensory neuronal model: relevance to cough hypersensitivity?. Issue 3 (21st September 2017) - Clarke, Rebecca; Monaghan, Kevin; About, Imad; Griffin, Caoimhin S.; Sergeant, Gerard P.; El Karim, Ikhlas; McGeown, J. Graham; Cosby, S. Louise; Curtis, Timothy M.; McGarvey, Lorcan P.; Lundy, Fionnuala T.
The cough reflex becomes hyperresponsive in acute and chronic respiratory diseases, but understanding the underlying mechanism is hampered by difficulty accessing human tissue containing both nerve endings and neuronal cell bodies. We refined an adult stem cell sensory neuronal model to overcome the limited availability of human neurones and applied the model to study transient receptor potential ankyrin 1 (TRPA1) channel expression and activation. Human dental pulp stem cells (hDPSCs) were differentiated towards a neuronal phenotype, termed peripheral neuronal equivalents (PNEs). Using molecular and immunohistochemical techniques, together with Ca 2+ microfluorimetry and whole cell patch clamping, we investigated roles for nerve growth factor (NGF) and the viral mimic poly I:C in TRPA1 activation. PNEs exhibited morphological, molecular and functional characteristics of sensory neurons and expressed functional TRPA1 channels. PNE treatment with NGF for 20 min generated significantly larger inward and outward currents compared to untreated PNEs in response to the TRPA1 agonist cinnamaldehyde (p<0.05). PNE treatment with poly I:C caused similar transient heightened responses to TRPA1 activation compared to untreated cells. Using the PNE neuronal model we observed both NGF and poly I:C mediated sensory neuronal hyperresponsiveness, representing potential neuro-inflammatory mechanisms associated with heightened nociceptive responses recognised in cough hypersensitivity syndrome. Development of a novel human adult stem cell neuronal model to investigate neural hyperresponsiveness in cough http://ow.ly/Ilvb30eokUC